Low-temperature crystallization preparation method of sol-gel metal oxide film

Through microwave-excited oxygen plasma treatment, the problem of difficult metal oxide films to crystallize under low temperature conditions is solved, and the preparation of high-quality films at low temperatures is realized, which is suitable for microelectromechanical systems and flexible substrates.

CN119633436AInactive Publication Date: 2025-03-18BEIJING INST OF TECH
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411772312.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to achieve the crystallization of metal oxide films under low temperature conditions, which limits its application in microelectromechanical systems and flexible substrates.

Method used

By using microwave-excited oxygen plasma to treat the metal oxide film, the removal of organic matter, gel condensation and film densification are achieved, thereby reducing the crystallization temperature of the oxide, avoiding the growth of high-temperature grains, and obtaining grains less than 5nm.

Benefits of technology

Low-temperature crystallization of metal oxide films (≤300℃) is achieved, and excessive grain problems caused by high-temperature treatment are avoided, and high-density and high-quality metal oxide films are obtained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633436A_ABST
    Figure CN119633436A_ABST
Patent Text Reader

Abstract

The invention relates to a low-temperature crystallization preparation method of a sol-gel metal oxide film, and belongs to the technical field of metal oxide films and sol-gel. Firstly, sol containing metal salt is prepared; then spin-coating the sol on the surface of a clean substrate, standing and curing, and forming an amorphous film on the surface of the substrate; and putting the substrate into a microwave plasma chamber, enabling the amorphous film surface to face upwards, and processing the film by using oxygen plasma to obtain the crystalline metal oxide film. Microwave is selected as an oxygen plasma excitation source, low temperature is kept by adjusting power and pressure intensity, and general preparation of the high-quality metal oxide thin film is achieved by combining the advantages that components of a sol-gel method are adjustable and large-area preparation is easy to achieve.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a low-temperature crystallization preparation method of a sol-gel metal oxide film, belonging to the technical field of metal oxide films and sol-gel. Background Art

[0002] Sol-gel, as a solution chemical synthesis method, has the advantages of adjustable composition, uniformity and high purity. Secondly, the rheological properties of the solution make it possible to prepare thin films by spin coating and dipping, which is low-cost, has strong substrate applicability, and is easy to achieve large-area thin film preparation. However, sol-gel usually requires heat treatment to achieve pyrolysis of organic compounds, as well as subsequent crystallization and sintering of materials. For metal oxides, the strong electron correlations imposed by the lattice determine their electrical, magnetic and optical properties, and crystallization (usually >500°C) is required to realize the full potential of their physical properties. This heat treatment limits the application in micro-electromechanical systems (MEMS) and flexible substrates. Usually MEMS is based on silicon microfabrication at low temperature (≤250°C), while for low-melting-point flexible substrates, in the most favorable case (polyimide), the temperature resistance is about 350°C. Therefore, how to achieve low-temperature crystallization of metal oxide films is crucial.

[0003] Among the existing low-temperature routes, one is to anneal at a temperature that is resistant to the flexible substrate to obtain an amorphous phase that can meet the use requirements. The second is to assist annealing by irradiating the film with ultraviolet (UV). By photochemically decomposing organic matter in the deposited layer by UV irradiation, a high-density metal-oxygen network can be obtained, and the prepared amorphous In-Ga-Zn-O film has a sufficient electron mobility value (about 3.8cm 2 s -1 V -1 ). Secondly, this method also reduces the temperature of subsequent heat treatment, such as PbTiO3 and BiFeO3 crystallized as low as 400°C. However, the above method reduces the crystallization temperature to a certain extent, but it obviously cannot solve the compatibility problem with silicon microfabrication and flexible substrates. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a low-temperature crystallization preparation method for a sol-gel metal oxide film. Crystallization is achieved by a method of low-temperature plasma-assisted treatment of a metal oxide film, and a microwave-excited oxygen plasma (maximum temperature only reaches 35°C) is used to treat the metal oxide film, and the removal of organic matter, condensation of the gel and densification of the film are achieved during the treatment process. During the plasma treatment process, the crystallization temperature of the oxide is effectively reduced, high-temperature grain growth is avoided, and grains <5nm are obtained.

[0005] To achieve the above objectives, the technical solution of the present invention is as follows.

[0006] A low-temperature crystallization preparation method of a sol-gel metal oxide film, the method steps comprising:

[0007] (1) preparing a sol containing a metal salt;

[0008] (2) Spin-coating the sol onto a clean substrate surface and allowing it to solidify to form an amorphous film on the substrate surface;

[0009] (3) The substrate is placed in a microwave plasma chamber with the amorphous film facing upward, and the film is treated with oxygen plasma to obtain a crystalline metal oxide film.

[0010] Preferably, the method further comprises: heat treating the film with a crystallization temperature above 400° C. More preferably, the heat treatment temperature is 200-300° C., the high temperature rate is 1-3° C. / min, and the holding time is 2-4 hours.

[0011] Preferably, the metal oxide includes titanium dioxide, yttrium stabilized zirconia (YSZ), high entropy oxide (CeLaPrNdSm)O 2-δ .

[0012] Preferably, in step (1), the metal salt, the complexing agent, the chemical additive for controlling drying and the solvent are stirred and mixed uniformly, the pH is adjusted to less than 7, and the sol is obtained after aging.

[0013] Preferably, when the metal oxide is titanium dioxide, the metal salt is tetrabutyl titanate; when the metal oxide is yttrium-stabilized zirconium oxide, the metal salt is zirconium oxychloride and yttrium nitrate; when the metal oxide is (CeLaPrNdSm)O 2-δ When the metal salt is cerium nitrate, lanthanum nitrate, praseodymium nitrate, samarium nitrate and neodymium nitrate.

[0014] Preferably, the complexing agent is one or more of citric acid, oxalic acid, acetic acid and ethanolamine.

[0015] Preferably, the additive is one or more of formamide, formamide, acetamide, propylene glycol and glycerol; and the molar ratio of the additive to the metal salt is 2 to 5:1.

[0016] Preferably, the solvent is one or more of water, ethanol, propanol and butanol.

[0017] Preferably, the concentration of the metal salt in the sol is 0.05 to 3 mol / L.

[0018] Preferably, the stirring rate is 200-300 rpm, and the stirring time is 20-40 min.

[0019] Preferably, in step (2), the thickness of the amorphous film is ≤300 nm to ensure that plasma can diffuse into the amorphous film.

[0020] Preferably, in step (2), when cleaning the substrate, the substrate is first ultrasonically cleaned with ethanol, and after drying, it is cleaned using microwave argon plasma at a plasma chamber pressure of 0.1 to 1 Torr, a power of 600 to 800 W, and a cleaning time of 2 to 10 minutes.

[0021] Preferably, in step (2), the spin coating speed is 4000-7000 rpm, and the spin coating time is 10-60 s.

[0022] Preferably, in step (3), the microwave plasma chamber pressure is 50-250 Torr, the power is 750-800 W, and the oxygen plasma temperature is 25-35°C.

[0023] Beneficial Effects

[0024] The present invention provides a low-temperature crystallization preparation method for a sol-gel metal oxide film. During the low-temperature oxygen plasma treatment process of the oxide film, reactive ions and free radicals diffuse into the film, oxidize the organic functional groups in the gel, promote further condensation and densification of the gel, and form a high-density metal-oxygen-metal (MOM) network. In addition, the high-energy electrons in the plasma provide additional energy for the ordered arrangement of atoms in the metal oxide, promoting crystallization. Therefore, for oxides with low crystallization activation energy, crystallization is achieved during the plasma treatment process, and for oxides with high crystallization activation energy, low-temperature crystallization (≤300°C) is achieved.

[0025] The present invention provides a low-temperature crystallization preparation method for a sol-gel metal oxide film. To avoid cracking of the film during plasma treatment, the sol needs to be adjusted to an acidic environment (pH <7). The polycondensation reaction rate is much greater than the hydrolysis rate through acid catalysis, forming a gel network with a low degree of crosslinking and a dense structure, thereby reducing the volume shrinkage caused by subsequent structural transformation. At the same time, a chemical additive for controlling drying is added, which is an organic liquid with a low vapor pressure. The low surface tension of the additive reduces the stress of the gel network when it shrinks.

[0026] The present invention provides a low-temperature crystallization preparation method for a sol-gel metal oxide film. The coupling efficiency between microwaves and plasma is close to 100%. The high-concentration electrons generated by the high operating frequency (2.45 GHz) of microwaves produce more active substances. At a power of 750 to 800 W and a pressure of 50 to 250 Torr, plasma at about 35° C. can be generated to promote film crystallization.

[0027] The present invention provides a method for preparing a metal oxide film with adjustable low-temperature synthesis components (multiple doping, multiple components), controllable crystallization degree, and adjustable mechanical, electrical, magnetic and optical properties. Metal oxides with multiple doping and multiple components can be achieved by introducing multiple metal salts into the solution through the sol-gel method. During the plasma treatment process, different treatment times can achieve different degrees of organic matter removal and atomic arrangement ordering. Therefore, different degrees of crystallization are exhibited in the plasma treatment time and the subsequent heat treatment temperature, and different mechanical, electrical, magnetic and optical properties are also achieved.

[0028] The present invention provides a method for preparing metal oxide thin films with low cost, simple process and wide adaptability. Microwave is selected as the excitation source of oxygen plasma, and the low temperature is maintained by adjusting the power and pressure. Combined with the advantages of adjustable components and easy large-area preparation of the sol-gel method, the universal preparation of high-quality metal oxide thin films is achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is the X-ray diffraction spectrum of the metal oxide film prepared in Example 1-3.

[0030] Figure 2 This is a scanning electron microscope image of the TiO2 film prepared in Example 1.

[0031] Figure 3 This is a scanning electron microscope image of the YSZ film prepared in Example 2.

[0032] Figure 4 is (CeLaPrNdSm)O prepared in Example 3 2-δ Scanning electron microscope image of the film. DETAILED DESCRIPTION

[0033] The present invention will be further described in detail below in conjunction with specific embodiments.

[0034] SEM characterization: The S-4800 cold field emission scanning electron microscope (SEM) produced by Japan Advanced Technology Corporation was used to characterize the microstructure of the samples to be tested.

[0035] XRD characterization: The crystal structure of the sample to be tested was characterized using a SmartLab grazing incidence X-ray diffractometer from Rigaku Corporation of Japan;

[0036] Tetrabutyl titanate: 99% purity, Shanghai MacLean Biochemical Technology Co., Ltd.;

[0037] Zirconium oxychloride: 99.9% purity, Shanghai MacLean Biochemical Technology Co., Ltd.;

[0038] Yttrium nitrate: 99.9% purity, Shanghai MacLean Biochemical Technology Co., Ltd.;

[0039] Cerium nitrate: 99.99% purity, Shanghai MacLean Biochemical Technology Co., Ltd.;

[0040] Lanthanum nitrate: 99.99% purity, Shanghai MacLean Biochemical Technology Co., Ltd.;

[0041] Praseodymium nitrate: 99.99% purity, Shanghai MacLean Biochemical Technology Co., Ltd.;

[0042] Samarium nitrate: 99.99% purity, Shanghai MacLean Biochemical Technology Co., Ltd.;

[0043] Neodymium nitrate: 99.9% purity, Shanghai MacLean Biochemical Technology Co., Ltd.;

[0044] Citric acid: 99.5% purity, Shanghai MacLean Biochemical Technology Co., Ltd.;

[0045] Acetic acid: 99.5% purity, Beijing Tongguang Fine Chemical Company

[0046] Nitric acid: AR 65-68%, Beijing Tongguang Fine Chemical Company

[0047] N,N-dimethylacetamide: 99.8% purity, Shanghai MacLean Biochemical Technology Co., Ltd.;

[0048] Microwave plasma cleaning machine: Plasma-PreenⅡ-862, Plasmatic Systems Co., Ltd.

[0049] Spin coater: KW-4A, Institute of Microelectronics, Chinese Academy of Sciences.

[0050] Example 1

[0051] (1) 1 mol of tetrabutyl titanate, 10 mol of ethanol, 5 mol of N,N-dimethylacetamide, 2.2 mol of nitric acid, 0.5 mol of acetic acid and 10 mol of deionized water were mixed, and mixed by magnetic stirring at a speed of 250 rpm for 30 min, and aged for 24 h to obtain a sol;

[0052] (2) The substrate was ultrasonically cleaned with ethanol for 10 min. The substrate was dried with a hair dryer and placed in a microwave plasma chamber. The substrate was cleaned with argon plasma at a power of 750 W, a chamber pressure of 3 Torr, and a cleaning time of 5 min.

[0053] (3) A thin film was prepared on the substrate surface by spin coating, wherein the sol was dropped onto the substrate surface using a dropper, the spin coating speed was 6000 rpm, the spin coating time was 10 s, and the film was allowed to stand in the air for 12 h to solidify.

[0054] (4) The sample was placed in a microwave plasma chamber with the film side facing upward and treated with oxygen plasma at a power of 750 W, a chamber pressure of 50 Torr, and a treatment time of 9 h.

[0055] The prepared TiO2 film has been obviously crystallized, the film quality is good, dense and without cracks.

[0056] Figure 1 The XRD test results show that anatase TiO2 is formed; Figure 2 The SEM test results show that the film is dense, uniform and crack-free. The grain size of the film obtained in this embodiment is 4.7 nm.

[0057] Example 2

[0058] (1) 1 mol of zirconium oxychloride, 1 mol of ethanol, 2 mol of N,N-dimethylacetamide, 0.087 mol of yttrium nitrate and 50 mol of deionized water were mixed, and mixed by magnetic stirring at a speed of 250 rpm for 30 min, and aged for 24 h to obtain a sol;

[0059] Steps (2) to (4) are the same as steps (2) to (4) in Example 1;

[0060] (5) The thin film sample after oxygen plasma treatment was placed in a muffle furnace and kept at 200°C for 3 h to obtain a well-crystallized YSZ thin film.

[0061] Figure 1 The XRD test results show that tetragonal YSZ is formed; Figure 3 The SEM test results show that the film is dense, uniform and crack-free. The grain size of the film obtained in this embodiment is 4.6 nm.

[0062] Example 3

[0063] (1) 0.4 mol of cerium nitrate, 0.4 mol of lanthanum nitrate, 0.4 mol of praseodymium nitrate, 0.4 mol of samarium nitrate, 0.4 mol of neodymium nitrate, 1 mol of citric acid, 2 mol of ethanol, 4 mol of N,N-dimethylacetamide and 100 mol of deionized water were mixed, and mixed by magnetic stirring at a speed of 250 rpm for 30 min, and aged for 24 h to obtain a sol;

[0064] Steps (2) to (4) are the same as steps (2) to (4) in Example 1;

[0065] (5) The film sample after oxygen plasma treatment was placed in a muffle furnace and kept at 300°C for 3 h to obtain a film.

[0066] Figure 1 The XRD test results show that the high entropy oxide (CeLaPrNdSm)O 2-δ The film has crystallized; Figure 4 The SEM test results show that the film is dense, uniform and crack-free. The grain size of the film obtained in this embodiment is 2.8 nm.

[0067] In summary, the invention includes but is not limited to the above embodiments. Any equivalent substitution or partial improvement made under the spirit and principle of the invention shall be deemed to be within the protection scope of the invention.

Claims

1. A method for preparing a sol-gel metal oxide thin film by low temperature crystallization, characterized in that: The method steps include: (1) preparing a sol containing a metal salt; (2) Spin-coating the sol onto a clean substrate surface and allowing it to solidify to form an amorphous film on the substrate surface; (3) The substrate is placed in a microwave plasma chamber with the amorphous film facing upward, and the film is treated with oxygen plasma to obtain a crystalline metal oxide film.

2. The method for preparing a sol-gel metal oxide thin film by low temperature crystallization according to claim 1, characterized in that: The method further comprises: heat treating the film with a crystallization temperature above 400°C; preferably, the heat treatment temperature is 200-300°C, the high temperature rate is 1-3°C / min, and the heat preservation time is 2-4h.

3. A method for preparing a sol-gel metal oxide thin film by low temperature crystallization according to claim 1 or 2, characterized in that: The metal oxides include titanium dioxide, yttrium-stabilized zirconium oxide, high entropy oxide (CeLaPrNdSm)O 2-δ .

4. A method for preparing a sol-gel metal oxide thin film by low temperature crystallization according to claim 1 or 2, characterized in that: In step (1), the metal salt, the complexing agent, the chemical additive for controlling drying and the solvent are stirred and mixed uniformly, the pH is adjusted to less than 7, and the sol is obtained after aging.

5. The method for preparing a sol-gel metal oxide thin film by low temperature crystallization according to claim 4, characterized in that: When the metal oxide is titanium dioxide, the metal salt is tetrabutyl titanate; when the metal oxide is yttrium-stabilized zirconium oxide, the metal salt is zirconium oxychloride and yttrium nitrate; when the metal oxide is (CeLaPrNdSm)O 2-δ When the metal salt is cerium nitrate, lanthanum nitrate, praseodymium nitrate, samarium nitrate and neodymium nitrate; The complexing agent is one or more of citric acid, oxalic acid, acetic acid and ethanolamine; The additive is one or more of formamide, formamide, acetamide, propylene glycol and glycerol; the molar ratio of the additive to the metal salt is 2 to 5:1; The solvent is one or more of water, ethanol, propanol and butanol. The concentration of the metal salt in the sol is 0.05-3 mol / L.

6. The method for preparing a sol-gel metal oxide thin film by low temperature crystallization according to claim 4, characterized in that: The stirring rate is 200-300 rpm, and the stirring time is 20-40 min.

7. A method for preparing a sol-gel metal oxide thin film by low temperature crystallization according to claim 1 or 2, characterized in that: In step (2), the thickness of the amorphous film is ≤300nm.

8. A method for preparing a sol-gel metal oxide thin film by low temperature crystallization according to claim 1 or 2, characterized in that: In step (2), when cleaning the substrate, the substrate is first ultrasonically cleaned with ethanol, and after drying, it is cleaned using microwave argon plasma at a plasma chamber pressure of 0.1 to 1 Torr, a power of 600 to 800 W, and a cleaning time of 2 to 10 minutes.

9. A method for preparing a sol-gel metal oxide thin film by low temperature crystallization according to claim 1 or 2, characterized in that: In step (2), the spin coating speed is 4000-7000 rpm, and the spin coating time is 10-60 s.

10. A low temperature crystallization method for preparing a sol-gel metal oxide thin film according to claim 1 or 2, characterized in that: In step (3), the microwave plasma chamber pressure is 50-250 Torr, the power is 750-800 W, and the oxygen plasma temperature is 25-35°C.

Citation Information

Patent Citations

  • Method for preparing metallic complex film

    CN101135052A

  • Rare earth doped cerium oxide material, preparation method and application thereof, and preparation method of infrared stealth coating

    CN117682545A

  • Method for preparing metal oxide film

    EP1164207A2

  • Production of superfine metal oxide particle

    JP1997100105A

  • Solgel binder solution and solution deposition therewith

    JP2000128645A